Pengaruh Stres Kerja dan Lingkungan Kerja Terhadap Kinerja Karyawan Generasi Z (Studi Kasus: PT XYZ) - Amelia Rahma Putri Avriany; Siti Mabrur Rachmah (JUMBIWIRA : Jurnal Manajemen Bisnis Kewirausahaan, 2025)
The dynamics of the modern workplace, driven by globalization and technological advancements, create significant challenges in human resource management, especially with the entry of Generation Z as a dominant workforce. This research is backgrounded by an observed phenomenon at PT XYZ, where there are indications of employee pressure arising from task mismatches and disturbances in the work environment. The objective of this study is to analyze the influence of work stress and work environment, both partially and simultaneously, on the performance of Generation Z employees. The research method employed is quantitative with a survey approach, utilizing a saturated sample of 98 employees. The main findings reveal that work stress and the work environment, both individually and collectively, have a significant influence on employee performance. Despite this significance, these two variables only account for 34.1% of the variance in performance, indicating a low level of influence. The implication of this study highlights the importance for the company to manage stress levels and foster a conducive work environment, while also underscoring the need for further research to identify other more dominant factors influencing the performance of Generation Z.